2016
DOI: 10.1002/ente.201600162
|View full text |Cite
|
Sign up to set email alerts
|

Concept Study for Competitive Power Generation from Chemical Looping Combustion of Natural Gas

Abstract: Chemical looping combustion (CLC) offers the possibility for efficient fuel conversion with inherent CO2 capture and is expected to significantly reduce the energy penalty associated with CO2 capture processes. Feasibility of the concept has been shown and studied thoroughly in lab experiments whereas the potential for power generation on a large scale will depend on the process configuration. Two different scenarios for competitive power generation from atmospheric pressure CLC of natural gas have been assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The residual capture penalty in CLC is related to the low-level process steam demand for loop seal fluidization and some additional blowers. The expected process steam demand for loop seal fluidization, based on an assessment of the CLC of natural gas for steam generation by Zerobin et al (2016), is assumed to be 5.3% of the fuel power input. The additional electric demand in CLC was earlier assessed as about 1% of the fuel power input compared to a natural gas-fired boiler (Zerobin et al 2016).…”
Section: Bioenergy With Carbon Capture and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…The residual capture penalty in CLC is related to the low-level process steam demand for loop seal fluidization and some additional blowers. The expected process steam demand for loop seal fluidization, based on an assessment of the CLC of natural gas for steam generation by Zerobin et al (2016), is assumed to be 5.3% of the fuel power input. The additional electric demand in CLC was earlier assessed as about 1% of the fuel power input compared to a natural gas-fired boiler (Zerobin et al 2016).…”
Section: Bioenergy With Carbon Capture and Storagementioning
confidence: 99%
“…The expected process steam demand for loop seal fluidization, based on an assessment of the CLC of natural gas for steam generation by Zerobin et al (2016), is assumed to be 5.3% of the fuel power input. The additional electric demand in CLC was earlier assessed as about 1% of the fuel power input compared to a natural gas-fired boiler (Zerobin et al 2016). For the present setting, where a CFB boiler for solid biomass is the benchmark, the additional electric demand for blowers and pumps is assumed to be 0.5% of the fuel power input.…”
Section: Bioenergy With Carbon Capture and Storagementioning
confidence: 99%
“…Marx et al (2013) reported for pilot plant test in a 10 MW th unit steam requirements for the fluidisation of the loop-seal to the fuel reactor and to the air reactor of 178.2 kg h −1 and 169.9 kg h −1 , respectively. It was assumed that through careful design of the loop-seals, the steam requirements in an industrial-scale process can be reduced by 50% (Zerobin et al 2016), which corresponds to a steam-to-oxygen carrier mass ratio of about 0.0257 for both loop-seals. To estimate the steam requirements for the CLAS process of this study, the value was linearly extrapolated to match the oxygen carrier circulation rate.…”
Section: The Chemical Looping Air Separation Systemmentioning
confidence: 99%
“…In the laboratory, cold flow models are widely used to study the hydrodynamics of CLC units with the goal of understanding and improving operating conditions (Markström and Lyngfelt, 2012;Penthor et al, 2016). Thereafter, designing and sizing are performed by using engineering tools and providing global quantities by bal ance investigations and process models (Bolhàr Nordenkampf et al, 2009;Marx et al, 2013;Ohlemüller et al, 2015;Zerobin et al, 2016;Zerobin et al, 2017;Haus et al, 2017). In order to model the CLC process and predict the CLC behavior, a one or one half dimensional model is employed because of its considerably low computational cost and previous successful results (Abad et al, 2010;Abad et al, 2013;García Labiano et al, 2013;Abad et al, 2014;Abad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%